137Cs activity in Sweden after the Chernobyl Nuclear Power Plant accident in relation to quaternary geology and land use. (December 2017) - Tondel, Martin; Granath, Göran; Wålinder, Robert
Abstract: After the Chernobyl Nuclear Power Plant accident 137 Cs was deposited in Mid-Sweden, with the highest activity in Gävle municipality. We compared aerial measurements of 137 Cs on the ground over time in Gävle municipality since 1986. Maps of soil types and land use were used to analyse the decrease in activity of 137 Cs. A spatial pattern was identified where the reduction of activity was greater in sand than in organic soil. For land use the reduction was greater in urban areas than in forests, with agricultural land in between. Long-term external radiation from 137 Cs depends not only on the physical decay of 137 Cs but also indirectly on geology, and this should be considered when calculating external radiation doses to individuals in epidemiological studies. Highlights: Interpolating maps on 137 Cs fallout, geology and land use generate new information. Soil type and land use influenced weathering of 137 Cs after the Chernobyl accident. Using pre-existing maps can be considered when predicting activity on the ground. Geology could be important to consider when estimating external radiation doses to man.